The CARMENES search for exoplanets around M dwarfs: variability of the He I line at 10 830 Å - Fuhrmeister, Birgit; Czesla, S.; Hildebrandt, L.; Nagel, E.; Schmitt, J. H. M. M.; Jeffers, S. V.; Caballero, J. A.; Hintz, D.; Johnson, E. N.; Schöfer, P.; Zechmeister, M.; Reiners, A.; et al. (Astronomy and astrophysics, 2020)
The He I infrared (IR) triplet at 10 830 Å is known as an activity indicator in solar-type stars and has become a primary diagnostic in exoplanetary transmission spectroscopy. He I IR lines are a tracer of the stellar extreme-ultraviolet irradiation from the transition region and corona. We study the variability of the He I triplet lines in a spectral time series of 319 M dwarf stars that was obtained with the CARMENES high-resolution optical and near-infrared spectrograph at Calar Alto. We detect He I IR line variability in 18% of our sample stars, all of which show Hα in emission. Therefore, we find detectable He I variability in 78% of the sub-sample of stars with Hα emission. Detectable variability is strongly concentrated in the latest spectral sub-types, where the He I lines during quiescence are typically weak. The fraction of stars with detectable He I variation remains lower than 10% for stars earlier than M3.0 V, while it exceeds 30% for the later spectral sub-types. Flares are accompanied by particularly pronounced line variations, including strongly broadened lines with red and blue asymmetries. However, we also find evidence for enhanced He I absorption, which is potentially associated with increased high-energy irradiation levels at flare onset. Generally, He I and Hα line variations tend to be correlated, with Hα being the most sensitive indicator in terms of pseudo-equivalent width variation. This makes the He I triplet a favourable target for planetary transmission spectroscopy.
Gesehen am 18.09.2020